Can contraction patterns predict neonatal outcomes?. (September 2014) - Frey, Heather A.; Tuuli, Methodius G.; Roehl, Kimberly A.; Odibo, Anthony O.; Macones, George A.; Cahill, Alison G.
Abstract Objective: To estimate the association between contraction patterns in labor and neonatal outcomes. Methods: A nested case–control study within a consecutive term birth cohort included women in labor with intrauterine pressure catheters (IUPCs) who reached the second stage. Cases were women delivering neonates with composite morbidity: special care or intensive care unit admission, umbilical artery pH ≤ 7.1 or 5-min Apgar < 7. The control group delivered without any components of the composite morbidity. Contraction frequency, duration, relaxation time, Montevideo units (MVUs) and baseline tone in the last 30 min prior to delivery were compared. We used logistic regression to adjust for potential confounders and receiver operating characteristic curves to evaluate the ability of contraction parameters to predict adverse neonatal outcomes. Results: There were 183 cases of adverse neonatal outcomes and 2172 controls without the composite outcome. Contraction duration, relaxation time, MVUs and baseline tone did not significantly differ between the groups. Tachysystole was more common in women with the adverse neonatal outcome (21% versus 15%, p = 0.01). A model including tachysystole, oxytocin use and nulliparity did not adequately predict the adverse outcome (AUC = 0.61). Conclusions: Although tachysystole is associated with adverse neonatal outcomes, uterine activity cannot be used to predict neonatal outcome.